Pemeriksaan Hemoglobin dan Penyuluhan Tanda Bahaya Kehamilan Pada Ibu Hamil Di Posyandu Batursari - Himatul Khoeroh; Nurlela Purnamasari; Nurjuliana Nurjuliana; Refi Meliawati; Rika Riyanti; Siska Marlina L; Sumargiyanti Sumargiyanti (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Hemoglobin (Hb) is an erythrocyte tetrameric protein that binds to non-protein molecules, namely the iron porphyrin compound called heme. Hb is one of the laboratory tests on pregnant women which can support the diagnosis or occurrence of complications in pregnant women, these complications can be detected through danger signs of pregnancy. Danger signs of pregnancy are signs that indicate dangers that can occur during pregnancy (antenatal), which if not detected can cause death. The aim of this community service is to facilitate Hb checks and to increase knowledge of pregnant women through education about the danger signs of pregnancy. The method of this activity is carried out by checking hemoglobin levels using the Sahli method and providing counseling using the discussion method to pregnant women about the danger signs of pregnancy and using the KIA book as the medium. This counseling was carried out at the Batursari Village Posyandu which was attended by 10 pregnant women. The results of the counseling showed that 8 pregnant women had normal Hb, 1 pregnant woman was in the mild anemia category, and 1 pregnant woman was in the severe anemia category. and after education regarding the danger signs of pregnancy, all pregnant women have good knowledge.